A cross sectional study on willingness and acceptance of postpartum sterilization by mothers at a tertiary hospital - Gunasingh, T. K. Shaanthy; Meena, T. S.; Mothilal, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India was the first country in the world to launch the Family Planning Programme in 1951. Despite this fact, India still lags behind in practicing contraception and limiting family size. Even though various measures for encouraging the usage of contraception have been taken up, the achievement in this field is not up to the expectation due to various social and cultural factors. The aim of our study is to estimate the prevalence of awareness, willingness and acceptance of postpartum sterilization among mothers who delivered with two and more children before discharge at a tertiary hospital. Methods: It is a cross sectional study using the survey data on uncovered mothers who are discharged without accepting sterilization and mothers who underwent sterilization in a tertiary hospital. Results: Total number of mothers with 2 and more living children was 231. All the mothers were aware of female sterilization method. Only 38.5% mothers underwent sterilization. 66.9% of mothers stated willingness for sterilization but not done among the uncovered mothers with 2 and more children. This disparity was due to various medical reasons (pediatric opinion 57.7%, anesthetist opinion 0.7%, not treated within 7 days of delivery 8.5%). Conclusions: In our study, the awareness of female sterilization in women was 100%. 79.6% of them were willing for sterilization. Women willing for sterilization were more in caesarean section (45.4%) than in women who delivered vaginally (34.2%).